Impacto da implantação do sistema integração lavoura–pecuária–floresta em latossolo de Cerrado - Silveira, André Luiz Rodrigues da (2016)
The current situation requires actions to promote development with minimal negative impact on the environment. Agriculture is a sector of the economy that directly interacts with and depends on the natural ecosystem, requiring energy and natural resources. In this respect there is a negative balance for the environment: the intense emission GHG, the soil resource is grately degraded and natural forests are diminished. Investment has to be made in technologies that contribute to stop this process. The recently promoted integrated Crop-Livestock-Forest production systems (iCLFs), in addition to their other desirable socio-economic impacts, are expected to favor the accumulation of soil organic matter and the recovery of degraded areas, a contributing factor to avoid deforestation for opening new areas for agriculture. We present two studies investigating the effect of an iCLF three years after its implementation upon degraded pasture (DP), in southern Goiás State of Brazil, in the savannah ecosystem (Cerrado) that was carried out in colaboration with the Boa Vereda Farm near the city of Cachoeira Dourada, where the iCLF and the reference management systems, conventional pasture (CP) and an recovered pasture (RP) were implemented. In the first study the effect of the implementation of the iCLF, upon DP was investigated on the total organic carbon (TOC) and total nitrogen (TN) accumulation in the soil. For that, besides TOC and N concentrations, soil texture, bulk density (Ds) and δ¹³C were evaluated to validate the comparability of the investigated areas under the different management systems on the stock of TOC and N. The soil samples were collected to 1.0 m depth in eight layers following a transect of five sampling points (repetitions). In the iCLF each sampling point had six soil profiles placed in different positions to represent situations according to the presence or not of trees and transition zones between trees and pasture. In the second study the samples were collected in the previous sampling scheme. The samples were collected down to 0.4m in 5 layers to evaluate the physical quality of the soil: bulk density (Ds), microporosity (Mi), macroporosity (Ma), total porosity (Pt), resistance to penetration (RP). The results of the first study showed that the management used during the implementation of iLPF, which included soil tillage with disc plowing, influenced negatively the stock of C and N in the 0-0.3m layer. Another factor that likely influenced the input of C and N in the soil was the low productivityof the pasture, result of the shading by the eucalyptus trees (Eucalyptus urograndis) on the brachiária grass (Urochloa brizantha). Considering the layer of 0.0 - 1.0 m, the management did not influence the stock of TOC and N in the soil. In the second study the results showed the formation of four groups on the basis of soil physical quality, and within the iLPF there was the formation of two groups that were distinguished by the presence or absence of trees. The presence of the trees in the iCLF created variation of the RP and Pt in relation to the pasture of the iCLF. This may be related to the increase in the volume of roots and more frequent trampling by the animals under the trees causing a reduction in the pore space and consequently greater RP. A complete cycle of the iCLF system usually ends with the cutting and replanting of trees after 5-7 years, depending on the purpose of the production. Therefore, further studies are necessary to evaluate the potential of the iCLF to accumulate TOC and N in the soil and their impact on its physical quality at the end of its cycle and eventually, after several cycles of the system.